The Role of Morality in the Formation of Individual Character According to the Qur'an: A Case Study on the Surahs That Regulate Social Ethics - Maharani (Journal of Scientific Studies and Multidisciplinary Research, 2025)
This study examines the role of morality in the formation of individual character from the Qur'anic perspective, focusing on surahs that regulate social ethics. The purpose of the research is to analyze how moral values in the Qur'an, particularly those addressing social ethics, contribute to shaping individual character in a social context. Using a descriptive qualitative approach, this study involved a thematic analysis of selected surahs—Surah Al-Baqarah, Surah Al-Hujurat, and Surah Luqman. Data was collected through a literature review of relevant Qur'anic exegeses and secondary sources on character education and Islamic ethics. The findings reveal that the Qur'an emphasizes the importance of moral guidance in fostering a strong relationship with God, promoting social harmony, and shaping an individual’s character. Surah Al-Baqarah focuses on perseverance and sincerity in worship, Surah Al-Hujurat addresses social interaction principles such as respect and mutual understanding, and Surah Luqman offers moral education, particularly in the family setting. The study suggests that these teachings are essential for forming responsible individuals who contribute to a just and prosperous society. The research highlights the relevance of Qur'anic ethics in the contemporary context of character education and offers practical insights for applying these moral principles in modern life.